2022
DOI: 10.3390/cancers14071648
|View full text |Cite
|
Sign up to set email alerts
|

CT-Based Radiomics Analysis to Predict Histopathological Outcomes Following Liver Resection in Colorectal Liver Metastases

Abstract: Purpose: We aimed to assess the efficacy of radiomic features extracted by computed tomography (CT) in predicting histopathological outcomes following liver resection in colorectal liver metastases patients, evaluating recurrence, mutational status, histopathological characteristics (mucinous), and surgical resection margin. Methods: This retrospectively approved study included a training set and an external validation set. The internal training set included 49 patients with a median age of 60 years and 119 li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 50 publications
(66 reference statements)
1
24
0
Order By: Relevance
“…Several previous researches demonstrated that wavelet features were significantly correlated with heterogeneity indices at the cellular level, which were promising radiomic features to evaluate prognosis in colorectal liver metastases patients (37). In this study, the radiomic signature that we constructed showed a reliable model to predict MMR status in GC, outperforming traditional semantic features extracted by radiologists.…”
Section: B C Amentioning
confidence: 75%
“…Several previous researches demonstrated that wavelet features were significantly correlated with heterogeneity indices at the cellular level, which were promising radiomic features to evaluate prognosis in colorectal liver metastases patients (37). In this study, the radiomic signature that we constructed showed a reliable model to predict MMR status in GC, outperforming traditional semantic features extracted by radiologists.…”
Section: B C Amentioning
confidence: 75%
“…Accurate diagnosis and staging of HCC can be achieved by CT ( Figure 3 ) or MRI ( Figure 4 ) in the absence of invasive methods, when precise and stringent criteria are applied [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. Although MRI proves to be more sensitive in the characterization of liver lesions, particularly with hepatospecific contrast agents, there is no unambiguous indication from the pool of experts [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 ].…”
Section: Li-radsmentioning
confidence: 99%
“…Accurate diagnosis and staging of HCC can be achieved by CT (Figure 3) or MRI (Figure 4) in the absence of invasive methods, when precise and stringent criteria are applied . Although MRI proves to be more sensitive in the characterization of liver lesions, particularly with hepatospecific contrast agents, there is no unambiguous indication from the pool of experts [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148]. The choice to use CT rather than MRI remains at the discretion of individual institutions.…”
Section: Ct/mri Li-radsmentioning
confidence: 99%
“…In the correct radiological disease management, multimodality imaging, including ultrasound (US), Computed Tomography (CT) and Magnetic Resonance Imaging (MRI), should also be preferred concerning the different phases of DTs approaches [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. In fact, during radiologist work-up, different moments may be considered: detection and characterization, adjacent structures involvement assessment, treatment response evaluation and surveillance [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. During each of these moments, the different techniques can be associated with and/or follow each other.…”
Section: Imagingmentioning
confidence: 99%